[(-15):(-5)-(-12):(-4)];(-294)=
[(-25):(-5):(-1)+(-20):(-4)-(-30):(-6)]:(-5)
Răspunsuri la întrebare
Răspuns de
2
[(-15):(-5)-(-12):(-4)];(-294)=[ 3 +12 :( -4) ] : (-294) = [ 3-3 ] :( -294) =0 :(-294) =0
[(-25):(-5):(-1)+(-20):(-4)-(-30):(-6)]:(-5)=[(-25):(-5):(-1)+(-20):(-4)-(-30):(-6)]:(-5)=[5:(-1)+5-5]:(-5)
=(-5+5-5):(-5)
=(-5):(-5)
=1
[(-25):(-5):(-1)+(-20):(-4)-(-30):(-6)]:(-5)=[(-25):(-5):(-1)+(-20):(-4)-(-30):(-6)]:(-5)=[5:(-1)+5-5]:(-5)
=(-5+5-5):(-5)
=(-5):(-5)
=1
Alte întrebări interesante
Matematică,
8 ani în urmă
Chimie,
8 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă